Studying the effects of fish muscle incorporation on storage stability of a novel corn-fish snack - Shahmohammadi, Hamid Reza; Bakar, Jamilah; Abdul Rahman, Russly; Mohd Adzhan, Noranizan; Mirhosseini, Hamed (Wiley Periodicals, 2016)
To investigate the effect of minced fish incorporation on storage stability of a puffed corn-fish snack, treatments including 15% silver carp (Hypophthalmichthys molitrix) meat and 85% corn (seasoned and unseasoned) were produced by a twin screw extruder. The peroxide values (PVs) of treatments increased (P < 0.05) with storage time and reached a peak in the 12th week, then the values declined following a quadratic model. The fish was the least significant factor (P < 0.05), meaning that incorporation of minced fish slightly affected the PV. Conversely, the seasoning was the most significant factor (P < 0.05) followed by storage time. The total volatile base nitrogen and free fatty acid concentration of treatments increased linearly during storage. No significant difference (P > 0.05) was found for crispiness and color. Also, no microbial growth was observed during storage. The storage stability of the seasoned corn-fish snack and the control was obtained 28 and 33 weeks, respectively.